School Culture: Its Relationship with Teachers’ Commitment - Lily James Billy; Muhamad Suhaimi Taat (2020)
Teachers’ commitment is very important to ensure the student excel as stated in Malaysian Education Blueprint 2013-2025. This research was to identify the relationship between school culture and teachers’ commitment in upper interior division of Sabah. This non-experimental study used a survey method and combined three probability sampling techniques in obtaining samples. Data were collected using two sets of adapted questionnaires from the TCM Employee Commitment Survey (Meyer & Allen , 2004) and organizational culture questionnaire (Ipek, 1999) and administered to 458 teachers. The data were analysed using the IBM SPSS Statistical 25.0 software. Based on descriptive analysis, school culture was at high level while teachers’ commitment was at moderate level. Based on the inferential analysis, t- test based on school culture showed insignificant finding (t=1.434, df= 456, p>0.05), which indicated there was no difference school culture based on gender. While t- test based on teachers’ commitment showed significant finding (t= 2.018, df= 456, p<0.05), which showed there was a difference teachers’ commitment based on gender. Through a Pearson Correlation test, there was a significant positive relationship between school culture and teachers’ commitment with average strength (r=0.427, p<0.01). This study suggests teachers to have high level of school culture as it will increase the teachers’ commitment.